Obustronny guz chromochłonny u dziecka objawiający się ostrym bólem brzucha. Opis przypadku - Raoudha, Kebaili; Amel, Tej; Nesrine, Jaballah; Najla, Soyah; Samia, Belhassen; Sana, Mosbahi; Jihene, Bouguila; Abdellatif, Nouri; Samia, Tilouche; Lamia, Boughamoura (Pediatric Endocrinology Diabetes and Metabolism, 2021)
Pheochromocytoma is a rare tumor during childhood, originating from the chromafine tissue. The clinical presentation can be variable and assembling many other diseases. This tumor submits specific care problems. We report the case of a 7-year-old boy who presented with headache, fever, abdominal pain and vomiting evolving for 3 days. The physical examination revealed a painful abdomen, a high blood pressure and profuse sweating. As an acute appendicitis was suspected, abdominal ultrasound then abdominal CT were performed, revealing multiple bilateral adrenal masses. Measurement of 24-hour urinary catecholamines showed a marked increase in normetanephrines: 7,18 mg/24 h (normal range: 0.07–0.46 mg/24 h). The MIBG scintigraphy revealed a bilateral fixation in the two adrenals. During the next weeks, the patient developed close peaks of threatening hypertension, controlled with difficulty through the concomitant use of three anti hypertensive treatments. He underwent surgery two months after the first consultation, and had a total adrenalectomy on the right side and subtotal on the left side. The pathological examination concluded with multiple and bilateral pheochromocytomas with a PASS score between 2 and 6. The patient was treated with hormone replacement therapy immediately after the surgery. The subsequent course with a 10-month follow-up was favorable with disappearance of functional signs, correct blood pressure, good general condition, normal growth and a normal biological balance.